Implementasi Sistem Keamanan WPA2-PSK pada Jaringan WiFi - Baihaqi .; Yeni Yanti; Zulfan . (Fakultas Teknik, 2018)
Nowadays the use of WiFi network technology device has been widely developed around the world, both used for voice and data communications. WiFi networks utilize high frequencies to deliver and connect a communication, then the vulnerability to security is also higher than with other communication technologies. Various security measures can be done through communication devices used by users or by operators who provide communication services. However, with the user who utilizes WiFi network technology, it can provide little security hole that can be exploited by the attacker. Then the attacker can find out the WPA2-PSK security password when the user connects to the WiFi network. So the resulting password through several techniques and testing used. Among them by utilizing the user connected to the WiFi network, testing fake SSID and testing WPS PIN. However, in this study only conducted testing through a user connected to a WiFi network. This technique and testing is solely done to penetrate the security of WiFi network, which aims to know the password of WPA2-PSK on WiFi network and to add insight about WiFi network security